Implications of heat stress-induced metabolic alterations for endurance training - Bennett, S.; Tiollier, E.; Owens, D. J.; Brocherie, F.; Louis, J. B. (International Journal of Sports Medicine, 2024)
Inducing a heat-acclimated phenotype via repeated heat stress improves exercise capacity and reduces athletes risk of hyperthermia and heat illness. Given the increased number of international sporting events hosted in countries with warmer climates, heat acclimation strategies are increasingly popular among endurance athletes to optimize performance in hot environments. At the tissue level, completing endurance exercise under heat stress may augment endurance training adaptation, including mitochondrial and cardiovascular remodeling due to increased perturbations to cellular homeostasis as a consequence of metabolic and cardiovascular load, and this may improve endurance training adaptation and subsequent performance. This review provides an up-to-date overview of the metabolic impact of heat stress during endurance exercise, including proposed underlying mechanisms of altered substrate utilization. Against this metabolic backdrop, the current literature highlighting the role of heat stress in augmenting training adaptation and subsequent endurance performance will be presented with practical implications and opportunities for future research.